Effect of Red Light-Emitting Diodes Irradiation on Hemoglobin for Potential Hypertension Treatment Based on Confocal Micro-Raman Spectroscopy. (12th January 2017) - Qiu, Xuejun; Huang, Hanchuan; Huang, Zhitong; Zhuang, Zhengfei; Guo, Zhouyi; Liu, Songhao
Abstract : Red light-emitting diodes (LED) were used to irradiate the isolated hypertension hemoglobin (Hb) and Raman spectra difference was recorded using confocal micro-Raman spectroscopy. Differences were observed between the controlled and irradiated Hb by comparing the spectra records. The Raman spectrum at the 1399 cm −1 band decreased following prolonged LED irradiation. The intensity of the 1639 cm −1 band decreased dramatically in the first five minutes and then gradually increased in a time-dependent manner. This observation indicated that LED irradiation increased the ability of oxygen binding in Hb. The appearance of the heme aggregation band at 1399 cm −1, in addition to the oxygen marker band at 1639 cm −1, indicated that, in our study, 30 min of irradiation with 15.0 mW was suitable for inhibiting heme aggregation and enhancing the oxygen-carrying capacity of Hb. Principal component analysis showed a one-to-one relationship between irradiated Hb at different time points and the corresponding Raman spectra. Our approach could be used to analyze the hemoglobin from patients with confocal micro-Raman spectroscopy and is helpful for developing new nondrug hypertension therapy.